Asymmetric Synthesis of d-Proline, d-Pipecolic Acid, (2R,3S,4R)-3,4-Dihydroxyproline, and 1,4-Dideoxy-1,4-imino-d-talitol from a Common Precursor - Chattopadhyay, Shital K.; Mukherjee, Jyoti Prasad (Synthesis, 2014)
Methodology involving stereoselective aza-Michael addition and ring-closing metathesis as key steps has been developed for the preparation of (2R)-pipecolic acid, (2R)-proline, (2R,3S,4R)-3,4-dihydroxyproline, and the known glycosidase inhibiting azasugar 1,4-dideoxy-1,4-imino-d-talitol from a common starting material namely (R)-cyclohexylideneglyceraldehyde in good overall yields.
Keywords: amino acids; chiral pool; metathesis; Michael addition; stereoselective synthesis